2019
DOI: 10.1007/s13167-019-00188-9
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence supported patient self-care in chronic heart failure: a paradigm shift from reactive to predictive, preventive and personalised care

Abstract: Heart failure (HF) is one of the most complex chronic disorders with high prevalence, mainly due to the ageing population and better treatment of underlying diseases. Prevalence will continue to rise and is estimated to reach 3% of the population in Western countries by 2025. It is the most important cause of hospitalisation in subjects aged 65 years or more, resulting in high costs and major social impact. The current “one-size-fits-all” approach in the treatment of HF does not result in best outcome for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
98
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 120 publications
0
98
0
2
Order By: Relevance
“…Studies have shown that predictive care is effective in critically ill and surgical patients. However, the application and research of predictive nursing in patients with allo-HSCT during perioperative period is still lacking [4,10].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that predictive care is effective in critically ill and surgical patients. However, the application and research of predictive nursing in patients with allo-HSCT during perioperative period is still lacking [4,10].…”
Section: Discussionmentioning
confidence: 99%
“…Methods from the field of artificial intelligence (AI), and more specifically machine learning, pose a great opportunity to drive the transition towards the PPPM paradigm [9]. These methods involve the use of biomedical data to build (i.e., "train") models which are capable of addressing a plethora of problems encountered in health research: Given a suitable data, they can assist diagnosis [10], model disease progression [11], identify patient subgroups for stratification [12], analyze survival chances [13], assist disease monitoring, and support appropriate therapies and medication [14].…”
Section: Artificial Intelligence As a Powerful Instrument To Implemenmentioning
confidence: 99%
“…The diversity of AI development teams will mandate interdisciplinary integration to achieve adoption, utility, safety, and inclusion all under the auspices of a new philosophy of care-AI-enabled care. 11 Although the landscape of HF care may be changing, the patient-doctor relationship will not be entirely replaced by AI. However, those who do not use AI will, in all probability, be replaced by those who do.…”
mentioning
confidence: 99%
“…Artificial intelligence (AI), a rapidly evolving field in medicine, especially cardiology, is revolutionizing risk prediction and stratification, diagnostics, precision medicine, workflows, and efficiency 8–10 . In a strategic paper, we [PAtient Self‐care uSing eHealth In chrONic Heart Failure (PASSION‐HF) consortium] propose using digital therapeutics powered by AI as a personalized approach to HF self‐care 11 . PASSION‐HF aims to develop a virtual ‘doctor at home’ system.…”
mentioning
confidence: 99%
See 1 more Smart Citation